Prognostic risk factors analysis of low-grade gastric intraepithelial neoplasia—a single-center follow-up study - Jiang, Xin; Miao, Ziting; Chen, Xuyu; Xia, Jianlei; Zhou, Bengang; Chen, Yuanyuan; Fang, Jingwen; She, Qiang; Li, Yaoyao; Zhang, Min; Ding, Yanbing (Frontiers in Medicine, 2025)
ObjectiveLow-grade gastric intraepithelial neoplasia (LGIN), as a precancerous lesion of gastric cancer, is of great significance in the prevention and treatment of gastric cancer. In this study, we investigated the risk factors associated with LGIN through the follow-up of LGIN patients, and provided a reliable basis for the clinical management of LGIN patients and the formulation of individualized clinical diagnosis and treatment strategies.MethodsA total of 283 patients, newly diagnosed with LGIN, were enrolled in the study. The regression of LGIN among these patients was assessed by comparing their gastroscopic and pathological findings before and after a rigorous follow-up period. The cohort was then stratified into a progressive group and a non-progressive group. Univariate analysis and multivariate logistic regression analysis were employed to investigate the potential risk factors contributing to the progression of LGIN in these patients.ResultsAmong 283 LGIN patients, 8.1% demonstrated lesion progression. Notably, five cases progressed to adenocarcinoma, resulting in an overall cancer incidence rate of 1.8%. Various factors, including age, gender, family history of gastrointestinal tumors, history of alcohol consumption, preference for pickled foods, preference for strong tea, H. pylori infection, lesion location, and endoscopic lesion manifestation, were found to be correlated with the progression of LGIN (p < 0.05). Multifactorial logistic regression analysis further elucidated that a history of alcohol consumption (p = 0.022, OR = 3.224, 95% CI: 1.183–8.782), a family history of gastrointestinal tumors (p = 0.029, OR = 3.526, 95% CI: 1.136–10.947), combined with H. pylori infection (p = 0.024, OR = 4.220, 95% CI: 1.205–14.783), lesion location in the cardia/gastric fundus (p = 0.004, OR = 6.838, 95% CI: 1.874–24.958), and endoscopic manifestation of an ulcerated indurated type (p = 0.023, OR = 5.073, 95% CI: 1.245–20.667) emerged as significant risk factors for lesion progression in LGIN patients.ConclusionLGIN patients with a history of alcohol consumption, a family history of gastrointestinal tumors, a combination of H. pylori infection, and lesions located in the cardia/gastric fundus versus lesions endoscopically presenting as ulcerated depressions are more likely to progress to cancer. These risk factors provide a reliable basis for the clinical management of LGIN patients and the development of individualized clinical treatment strategies.